Shock Wave Structure in a Binary Mixture of Gases with a Rotational Degree of Freedom and Comparable Masses - Fiszdon, W.; Platkowski, T. (Engineering Transactions, 1977)
Plane stationary shock waves in a binary mixture of gases are considered. The first component of the mixture is monoatomic and the second is diatomic with a rotational degree of freedom. To obtain hydrothermodynamic. quantities, the modified BGK equations are solved using the Mott-Smith assumption. To close the set of equations, two moments of the BGK set of equations are taken. The hydrothermodynamic quantities are computed numerically and shock wave pro-files are found for different mass and density ratios of the two components. To investigate the influence of the rotational degree of freedom, a similar procedure is performed for the case of a binary mixture of monoatomic gases. The dependence of the shock structure on mass and density ratios as well as the rotational degree of freedom effects are shown.